Community Participation in the Development of Local Wisdom-Based Tourism Villages - Gustia, Gustia; Ahmad Said, M. Ridwan; Suhaeb, Firdaus W (CV. Eureka Murakabi Abadi, 2025)
This study aims to 1) analyze the forms of community participation in the development of local wisdom-based tourism villages in Paccekke Village, and 2) analyze the factors that influence community participation in the development of Local Wisdom-Based Tourism Villages in Paccekke Village. The method used in this study was qualitative, with observation, interview and documentation data collection techniques. The data analysis techniques used were data reduction, presenting data and drawing conclusions. The results of the study indicate that: 1) community participation had been quite active in the planning and implementation stages, indicated by involvement in village deliberations and contributions of manpower and materials in tourism village activities. However, participation is still lack at the stage of utilization of results and evaluation due to lack of socialization, unequal distribution of development benefits, and low sense of ownership. 2) Factors that encourage participation include the spirit of mutual cooperation, the active role of community leaders, and the use of technology. The obstacles to participation come from time constraints, minimal understanding of tourism, inadequate infrastructure conditions, and weak communication networks. Therefore, a strategy is needed to strengthen community capacity and synergy between stakeholders so that the development of tourism villages can be sustainable and bring economic, social and cultural benefits